Eficiência agronômica de fertilizantes nitrogenados, emissão de CO2 e volatilização de NH 3 na cultura do milho - Souza, Taylor Lima de (2015)
The increase in corn productivity implies a proper supply of nutrients, among which nitrogen (N) stands out. Urea is the most widely nitrogen fertilizer used in agriculture, it presents high concentration of N and less cost. The objective of this study was to evaluate the agronomic efficiency of conventional, stabilized, and slow and controlled release nitrogen fertilizers in corn crop. The experiment was conducted in Lavras, Minas Gerais state, Brazil. The treatments were: Prilled urea, granulated urea, urea incorporated into 2 cm deep, ammonium nitrate, sulfur coated urea (16% of elementary sulfur -S 0 ) urea + 530 mg kg -1 NBPT, Polymer coating of sulfur-coated urea (7.9% of S 0 + polymers), hydrolyzed leather, urea + thermoplastic resin. All fertilizers were applied at 150 kg ha -1 of N in top dressing and the control treatment (without nitrogen in topdressing).Were evaluated: Daily and cumulative CO2 emissions after 33 days from the application of nitrogen fertilizers, ammonia losses by volatilization, dry weight of shoots (straw), grain productivity, accumulation of nitrogen and sulfur in the grains and in straw and two agronomic efficiency index were calculated. The largest losses of N-NH3 from conventional urea (granulated or prilled) occur until the 7 th day of application in coverage. The Urea + NBPT, urea + 16% S 0 , urea + 7.9% + S 0 + polymers promoted delay and reduction in peak of ammonia volatilization. Hydrolyzed leather promoted greater emission of CCO2 compared to other nitrogen fertilizers. While the thermoplastic resin coated urea, ammonium nitrate and ammonium sulfate gave lower values of cumulative CO2 emission. The nitrogen fertilizers applied in topdressing promoted differences in the total accumulation of nitrogen and sulfur. Urea + thermoplastic resin and urea + S 0 + polymers promoted lower productivity and relative agronomic efficiency compared to other nitrogen fertilizers.